Pemanfaatan Teknologi Tentang Menghitung Denyut Jantung Janin Di Desa Tanakaraeng Kabupaten Gowa - Sutrani Syarif (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Monitoring the well-being of the fetus is an important thing to do during pregnancy, this is useful to be able to see the development of the fetus from time to time. The infant mortality rate is an important indicator to measure the health status of a country. This is because babies are very vulnerable to poor health or well-being. One way to reduce perinatal mortality caused by complications of fetal hypoxia in utero is by monitoring fetal well-being. The purpose of this activity is to increase the knowledge of pregnant women regarding the use of technology to calculate fetal heart rate. This activity was attended by 24 participants, during the implementation of the counseling, the presenters also conducted an evaluation by conducting a question and answer session with the counseling participants. This counseling gave significant results where there was an increase in knowledge of pregnant women by looking at the results of the evaluation given by conducting a question and answer session with counseling participants